Assessment Risk Factors Study for Bowel Anastomosis for Iraqi Patients - Dr. Mohammed Tareq Mohammed; Dr. Sabah kareem Oleiwi; Dr. Ali Ramzi Naji; Dr. Ali Qais Abdulkafi (Zien Journals, 2022)
Background: anastomotic leakage is one of the most dreaded surgical complications and is associated with increased morbidity, mortality, and hospitalization. Objective: This research aims to assessment risk factors study for bowel anastomosis for Iraqi patients. Materials and methods: a descriptive-analytical study was conducted in several hospitals in Iraq for the assessment of risk factors for Bowel Anastomosis for Iraqi Patients applied to 90 patients between the ages of 20 and 60 from May 2020 to October 2021
Keywords: Bowel Anastomosis; Leakage; Hypertension; Transverse colectomy